Analysis of Businnes Strategy in Bussiness Zozo Garden Bandar Lampung City with SWOT Matrix Approach - Jogi Putra Maulana; Muslimin Muslimin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The food and beverage industry in Indonesia has experienced rapid growth, leading to increasingly intense competition among cafés and restaurants and requiring businesses to formulate effective strategies to sustain competitiveness and long-term growth. This study aims to analyze the business strategy of Zozo Garden Coffee & Eatery, a garden-themed café located in Bandar Lampung, Indonesia, by evaluating its internal and external environments and identifying the most appropriate strategic priorities. A qualitative case study approach was employed using purposive sampling involving the owner, customers, and an industry expert as informants. Primary data were collected through observations, semi-structured interviews, and documentation, while secondary data were obtained from relevant literature. The collected data were analyzed using the Internal Factor Evaluation (IFE) Matrix, External Factor Evaluation (EFE) Matrix, Internal–External (IE) Matrix, SWOT Matrix, and Quantitative Strategic Planning Matrix (QSPM). The results show that Zozo Garden achieved an IFE score of 3.10 and an EFE score of 2.84, positioning the company in Cell IV (Grow and Build) of the IE Matrix. The QSPM analysis identified the SO1 strategy as the top priority with a Total Attractiveness Score (TAS) of 3.99, emphasizing digital marketing enhancement, brand differentiation, and customer experience improvement. The study concludes that growth-oriented strategies supported by continuous operational improvement are essential for strengthening competitiveness and ensuring long-term business sustainability.